2013
DOI: 10.5005/jp-journals-10024-1335
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Submucosal Injection of Dexamethasone on Postoperative Discomfort after Third Molar Surgery: A Prospective Study

Abstract: Submucosal route of administration of dexamethasone (4 mg) is effective in reducing postoperative discomfort after third molar surgeries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…Restriction of mouth opening can be caused by the splinting action of the investing muscles in an attempt to reduce discomfort upon jaw movement after surgery or due to the inflammation widespread involving the muscles of mastication with edema preventing its flexibility [27]. The time course for trismus and concurrent limitation in oral function described in the current study are in agreement with findings that indicated that trismus reaches a maximum on Day 1 or Day 2 postoperatively and generally resolve by Day 7 [11, 21]. After 7 days, group B showed statistically significantly higher mean% reduction in maximum interincisal opening value than group A (45.3 ± 1.5 in A, 44.2 ± 6.1 in B, p value , 0.527).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Restriction of mouth opening can be caused by the splinting action of the investing muscles in an attempt to reduce discomfort upon jaw movement after surgery or due to the inflammation widespread involving the muscles of mastication with edema preventing its flexibility [27]. The time course for trismus and concurrent limitation in oral function described in the current study are in agreement with findings that indicated that trismus reaches a maximum on Day 1 or Day 2 postoperatively and generally resolve by Day 7 [11, 21]. After 7 days, group B showed statistically significantly higher mean% reduction in maximum interincisal opening value than group A (45.3 ± 1.5 in A, 44.2 ± 6.1 in B, p value , 0.527).…”
Section: Discussionsupporting
confidence: 86%
“…Use of the corticosteroid, Dexamethasone, given by local [16], oral [11, 17, 18], intramuscular [19], intravenous, or submucosal [11, 17, 20, 21] routes, either preoperatively, perioperatively, or postoperatively appears to be effective in the prevention of postoperative edema. Long-acting steroids give better results than short-acting one and submucosal administration of steroids produces similar effects to intravenous and intramuscular routes [22].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the same are listed in [Table/ Fig-1] [14][15][16][17][18][19][20][21][22][23][24]. Most of these studies have administered corticosteroids preoperatively whereas in our study we administered it postoperatively.…”
Section: Resultsmentioning
confidence: 99%
“…The effect on QoL was comparable among the treatment groups in all parameters. Intravenous group showed the lowest scores followed by the submucosal group Nair et al (2013) [ 33 ] 100 Administered pre-emptive A. Dexamethasone 4 mg/submucosal ( n = 50) A. Control—no drug ( n = 50) Significantly less in Group A on Day 2 No significant difference between both groups No significant difference between both groups Warraich et al (2013) [ 34 ] 100 Administered pre-emptive A. Dexamethasone 4 mg/submucosal ( n = 50) B. Control—no drug ( n = 50) Significantly less in Group A on Day 2 and Day 10 Significantly less in Group A from Day 2 to Day 10 Significantly less in Group A on Day 2 Ehsan et al (2014) [ 35 ] 100 Administered pre-emptive A. Dexamethasone 4 mg/submucosal ( n = 50) B. Control—no drug ( n = 50) Significantly less in Group A on Day 2 Not studied Significantly less in Group A on Day 2 Agostinho et al (2014) [ 36 ] 54 Administered pre-emptive A. Dexamethasone 4 mg/oral ( n = 27) B. Dexamethasone 12 mg/oral ( n = 27) No significant difference between the two groups on Day 1 and Day 2 No significant difference between the two groups on Day 1 and Day 2 No significant difference between the two groups on Day 1 and Day 2 Marques et al (2014) [ 40 ] 50 Administered post-operative A. Bethamethasone 12 mg/submucosal ( n = 25) B. Control—saline injection ( n = 25) No significant difference between the two groups No significant difference between the two groups No significant difference between the two groups Chaudary et al (2015) [ 37 ] 200 …”
Section: Methodsmentioning
confidence: 99%